Regeneration potential of seedling explants of chilli (Capsicum annuum) - Md Ashrafuzzaman,; Hossain, Mohammad Mosharraf; Ismail, Mohd Razi; Haque, M. Shahidul; Shahidullah, S. M.; Shahin-uz-zaman, (Academic Journals, 2009)
A study was conducted with hypocotyl, cotyledon and shoot tip of chilli as explants for regeneration on MS medium supplemented with different concentrations and combinations of auxins and cytokinins. Regeneration potential was determined by two ways. One is regeneration of shoot via callus formation from hypocotyls and cotyledon explants; another was direct shoot regeneration from shoot tip explant. The highest callus was induced from hypocotyl in a combination of BAP (5.0 mgL-1) with NAA (0.1 mgL-1) and cotyledon in a combination of BAP (5.0 mgL-1) with IAA ((1.0 mgL-1). The callus induction as well as shoot initiation was higher in hypocotyls than cotyledon. Shoot tips regenerated into plantlets directly with sporadic small callus at the base. Shoot elongation was accelerated by using additional supplementation of GA3 and AgNO3. Regenerated shoots rooted best on the MS medium supplemented with 0.1 mg L-1 NAA + 0.05 mg L-1 IBA.